Exploring E-Commerce and Corporate Social Responsibility from the Sharia Point of View - Hossain, Mohammad Faruk; Md Ismail, Che Thalbi; Mahdzir, Nazli (iRASD, 2021)
This study discusses what is, and what is not a valid and legal contract in Sharia, considering certain stipulated requirements for the acceptability of a contract. It then considers the legality of ecommerce, whether it complies with those stipulated requirements. Business under Islam primarily fulfils a collective religious obligation and fulfil an enlarged scope of responsibilities. In this context, the protection of the e-consumers, the status of an ecommerce transaction and responsible e-commerce are discussed to expose to those who are wondering whether e-commerce is admissible from the Sharia point of view. So that they could benefit from e-commerce if it is proved as an admitted fact in Islam. The final section concludes with a plea for good judgment toward corporate social responsibility practice and avoiding prohibited materials in e-commerce